Effects of initial conditions on vortex-ring core trajectories - Yeo, Jovan Rui (Nanyang Technological University, 2021)
Elliptical vortex rings exhibit a phenomenon known as axis switching, in which a vortex ring’s major and minor axes interchange a certain distance from the origin of the jet. Such switching can happen once or may be repeated, depending on the initial conditions of the nozzle. While this phenomenon has been studied comprehensively in the high Reynolds number (Re) range, relatively little data is available for comparison for vortices formed in the low Reynolds number range. As such, this paper seeks to categorize the evolution of vortex rings created from elliptical nozzles with an aspect ratio of 2 to 4 in the low Reynolds numbers region (500 to 4000). Vortex rings were generated in a tank and the evolution of both axes within 7 equivalent diameters (70mm) was analyzed. The results showed that at lower Reynolds numbers, the axis switching instances are oscillatory in nature and occur closer to the nozzle than at higher Reynolds numbers. However, with a nozzle aspect ratio of 4, the vortex ring showed an early breakup at Re = 2000, with evidence that collapse was due to vortex bifurcation. At Re = 4000, that nozzle aspect ratio showed no coherent vortex for analysis. Such axis switching behavior has a wide range of applications due to its enhanced fluid mixing properties.